2018
DOI: 10.1111/den.13203
|View full text |Cite|
|
Sign up to set email alerts
|

Efficacy and safety of pancreatic juice cytology by using synthetic secretin in the diagnosis of pancreatic ductal adenocarcinoma

Abstract: Adding synthetic secretin to PJC is useful for cases in which it is difficult to carry out EUS-FNA for PDAC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 22 publications
(32 reference statements)
0
15
0
Order By: Relevance
“…ENPD was first implemented by Endo et al[ 64 ] in 1974 for cytodiagnosis of pancreatic cancer. A slight modification of the standard ENPD technique wherein pancreatic juice collection is performed after injection of synthetic secretin, has been shown to provide a dedicated sample with a sufficient number of cells for cytological analysis and has improved the diagnostic sensitivity from 50.9% to 70.4%[ 65 ]. Of note, in this study, an additional 13 pancreatic cancer patients were diagnosed using the modified ENPD technique that were missed with EUS-fine needle aspiration (EUS-FNA), making the modified ENPD technique preferred, particularly in instances where tissue collection with EUS-FNA is unsuccessful or impossible[ 65 ].…”
Section: Ercp-guided Diagnostic Interventionsmentioning
confidence: 99%
See 2 more Smart Citations
“…ENPD was first implemented by Endo et al[ 64 ] in 1974 for cytodiagnosis of pancreatic cancer. A slight modification of the standard ENPD technique wherein pancreatic juice collection is performed after injection of synthetic secretin, has been shown to provide a dedicated sample with a sufficient number of cells for cytological analysis and has improved the diagnostic sensitivity from 50.9% to 70.4%[ 65 ]. Of note, in this study, an additional 13 pancreatic cancer patients were diagnosed using the modified ENPD technique that were missed with EUS-fine needle aspiration (EUS-FNA), making the modified ENPD technique preferred, particularly in instances where tissue collection with EUS-FNA is unsuccessful or impossible[ 65 ].…”
Section: Ercp-guided Diagnostic Interventionsmentioning
confidence: 99%
“…A slight modification of the standard ENPD technique wherein pancreatic juice collection is performed after injection of synthetic secretin, has been shown to provide a dedicated sample with a sufficient number of cells for cytological analysis and has improved the diagnostic sensitivity from 50.9% to 70.4%[ 65 ]. Of note, in this study, an additional 13 pancreatic cancer patients were diagnosed using the modified ENPD technique that were missed with EUS-fine needle aspiration (EUS-FNA), making the modified ENPD technique preferred, particularly in instances where tissue collection with EUS-FNA is unsuccessful or impossible[ 65 ]. Another modification of ENPD involving placement of a 4 or 5 Fr tube (with 8-12 hole) in the main pancreatic duct and collection of pancreatic juice 2-6 times daily for up to 3 d has increased the diagnostic yield for detection of pancreatic cancer with 80% sensitivity, 100% specificity, 100% positive predictive value, 71% negative predictive value, and 87% overall accuracy[ 66 ].…”
Section: Ercp-guided Diagnostic Interventionsmentioning
confidence: 99%
See 1 more Smart Citation
“…25,26 These low values are attributed to difficulties associated with collecting a sufficient number of cells. Takeda et al 27 reported sensitivity of pancreas juice cytology by using synthetic secretin for pancreatic carcinoma improved from 50.9% to 70.4% compared to conventional method, and this method revealed 13 pancreatic carcinoma that had not been able to be diagnosed with EUS-FNA. In another report, Mikata et al 8 reported the use of 5-Fr or 6-Fr ENPD tubes placed in the pancreatic duct and retained for up to 3 days.…”
Section: Endoscopic Retrograde Cholangiopancreatographymentioning
confidence: 99%
“…Previous reports state that EUS-FNA has a sensitivity of approximately 85%-89% for pancreatic disease[23], 25%-100% for biliary duct disease[33-36], and a diagnostic power of 85.7% to 86.0% for SEL[37,38]. Techniques that are reportedly useful for supplementing this diagnostic power include pancreatic juice cytology for pancreatic disease[39-41], transpapillary bile duct biopsy, and bile cytology for biliary tract disease[42-44], and EUS-FNA with a forward-viewing linear echoendoscope for SEL[45], as well as endoscopic submucosal dissection and endoscopic snare resection[46-49].…”
Section: When Pathological Evidence Can Not Be Obtained With Eus-fnamentioning
confidence: 99%